A Fluorescence-Based Method for Rapid and Direct Determination of Polybrominated Diphenyl Ethers in Water - Huimei Shan; Chongxuan Liu; Zheming Wang; Teng Ma; Jianying Shang; Duoqiang Pan (Journal of Analytical Methods in Chemistry)
A new method was developed for rapid and direct measurement of polybrominated diphenyl ethers (PBDEs) in aqueous samples using fluorescence spectroscopy. The fluorescence spectra of tri- to deca-BDE (BDE 28, 47, 99, 153, 190, and 209) commonly found in environment were measured at variable emission and excitation wavelengths. The results revealed that the PBDEs have distinct fluorescence spectral profiles and peak positions that can be exploited to identify these species and determine their concentrations in aqueous solutions. The detection limits as determined in deionized water spiked with PBDEs are 1.71–5.82 ng/L for BDE 28, BDE 47, BDE 190, and BDE 209 and 45.55–69.95 ng/L for BDE 99 and BDE 153. The effects of environmental variables including pH, humic substance, and groundwater chemical composition on PBDEs measurements were also investigated. These environmental variables affected fluorescence intensity, but their effect can be corrected through linear additivity and separation of spectral signal contribution. Compared with conventional GC-based analytical methods, the fluorescence spectroscopy method is more efficient as it only uses a small amount of samples (2–4 mL), avoids lengthy complicated concentration and extraction steps, and has a low detection limit of a few ng/L.